2000
DOI: 10.1002/(sici)1522-2632(200004)85:2/3<253::aid-iroh253>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Quantitative Structure Activity Relationship (QSAR) of Dissolved Humic Substances as Detoxifying Agents in Freshwaters

Abstract: In freshwater ecosystems, dissolved humic substances (HS) can sorb hydrophobic organic chemicals and thereby reduce their bioconcentration and toxicity. The extent of the sorption depends both on the concentration and on the origin of HS. This paper summarizes work that characterized HS from different origins by various spectroscopic and chemical properties, and related these properties to (1) the sorption of polycyclic aromatic hydrocarbons (PAHs) by HS (measured by a fluorescence quenching method), (2) effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…These compounds share fluorene's basic molecular structure, only differing by one atom in the bridge of the furan ring: C in FLU, O in DBF, and S in DBT (Table 1). Like many PAHs, these compounds are sparingly soluble with low volatility and high K OW (Table 1) and in soils and sediments they strongly associate with dissolved or particulate organic matter [18][19] that may significantly increase apparent solubility [20] yet often reduce bioavailability and toxicity [21]. Interaction with precipitated organic matter may also reduce toxicity of PAHs [22].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds share fluorene's basic molecular structure, only differing by one atom in the bridge of the furan ring: C in FLU, O in DBF, and S in DBT (Table 1). Like many PAHs, these compounds are sparingly soluble with low volatility and high K OW (Table 1) and in soils and sediments they strongly associate with dissolved or particulate organic matter [18][19] that may significantly increase apparent solubility [20] yet often reduce bioavailability and toxicity [21]. Interaction with precipitated organic matter may also reduce toxicity of PAHs [22].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the structural characteristics of humic substances such as the charge and size distribution in combination with physicochemical properties derived from their secondary/tertiary structures, cause mobilization (via binding to dissolved organic carbon) and immobilization (via formation of bound residues) of pollutants in the ecosphere, thereby defining transport, bioavailability and toxicity. Many studies have confirmed the relations between active humic binding sites and their specific reactivity toward given structural models (Peuravuori 2001;Steinberg et al 2000). Affinity capillary electrophoresis (ACE) is an accepted method used to study analyte-ligand interactions in pharmacological studies with different types of components.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of suspended sediments may interact with pesticides and thereby influence their bioavailability and toxicity. It generally is believed that pesticides associated with suspended sediments are less bioavailable than their dissolved forms (e.g., [3,4]). On the other hand, suspended particles can reduce light penetration in surface water and inhibit photosynthesis of water plants.…”
Section: Introductionmentioning
confidence: 99%